T-bet over-expression regulates aryl hydrocarbon receptor-mediated T helper type 17 differentiation through an interferon (IFN)γ-independent pathway. (31st January 2017) - Yokosawa, M; Kondo, Y; Tahara, M; Iizuka-Koga, M; Segawa, S; Kaneko, S; Tsuboi, H; Yoh, K; Takahashi, S; Matsumoto, I; Sumida, T
Summary: Various transcription factors are also known to enhance or suppress T helper type 17 (Th17) differentiation. We have shown previously that the development of collagen-induced arthritis was suppressed in T-bet transgenic (T-bet Tg) mice, and T-bet seemed to suppress Th17 differentiation through an interferon (IFN)-γ-independent pathway, although the precise mechanism remains to be clarified. The present study was designed to investigate further the mechanisms involved in the regulation of Th17 differentiation by T-bet over-expression, and we found the new relationship between T-bet and aryl hydrocarbon receptor (AHR). Both T-bet Tg mice and IFN-γ –/– -over-expressing T-bet (T-bet Tg/IFN-γ –/– ) mice showed inhibition of retinoic acid-related orphan receptor (ROR)γt expression and IL-17 production by CD4 + T cells cultured under conditions that promote Th-17 differentiation, and decreased IL-6 receptor (IL-6R) expression and signal transducer and activator of transcription-3 (STAT-3) phosphorylation in CD4 + T cells. The mRNA expression of ahr and rorc were suppressed in CD4 + T cells cultured under Th-17 conditions from T-bet Tg mice and T-bet Tg/IFN-γ –/– mice. CD4 + T cells of wild-type (WT) and IFN-γ –/– mice transduced with T-bet-expressing retrovirus also showed inhibition of IL-17 production, whereas T-bet transduction had no effect on IL-6R expression and STAT-3 phosphorylation. Interestingly, the mRNA expression of ahr and rorc were suppressed in CD4 + T cells with T-bet transduction cultured under Th17 conditions. The enhancement of interleukin (IL)−17 production from CD4 + T cells by the addition of AHR ligand with Th17 conditions was cancelled by T-bet over-expression. Our findings suggest that T-bet over-expression-induced suppression of Th17 differentiation is mediated through IFN-γ-independent AHR suppression. Graphical Abstract: